Detection of failure mechanisms in 24–40 nm FinFETs with (spectral) photon emission techniques using InGaAs camera. (September 2018) - Vogt, I.; Nakamura, T.; De Wolf, I.; Boit, C.
Abstract: We present two comprehensive failure analysis case studies using (spectral) photon emission techniques on various 24–40 nm n-FinFETs of two tech generations. Different failure mechanisms within the FinFETs are discovered when investigating deeper into suspicious emission behaviour and spectra. The FA diagnosis is confirmed by electrical measurements for all FinFETs. The emission spectra even offer the opportunity to relate effects on the temperature of the hot electron gas within the channel to failure mechanisms. The obtained electron temperature slopes over drain voltage for 5 different gate lengths can be used to qualitatively and quantitatively determine the red-shift of FinFET emission intensities. The results clearly indicate that (spectral) photon emission analysis for FA can be carried out for modern low-voltage devices well below 1 V, contrary to the common opinion. Highlights: Successful failure analysis with photon emission (PE) on 24–40 nm low-voltage FinFETs of 2 different techs PE signals and spectra of FinFETs below 1 V over drain and gate voltage Carrier gas temperature of FinFETs between 500 and 900 K detected Red-Shift and approximation for PE signals above 1500 nm